If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(2x + 3) = 3x + 1 Reorder the terms: -1(3 + 2x) = 3x + 1 (3 * -1 + 2x * -1) = 3x + 1 (-3 + -2x) = 3x + 1 Reorder the terms: -3 + -2x = 1 + 3x Solving -3 + -2x = 1 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -3 + -2x + -3x = 1 + 3x + -3x Combine like terms: -2x + -3x = -5x -3 + -5x = 1 + 3x + -3x Combine like terms: 3x + -3x = 0 -3 + -5x = 1 + 0 -3 + -5x = 1 Add '3' to each side of the equation. -3 + 3 + -5x = 1 + 3 Combine like terms: -3 + 3 = 0 0 + -5x = 1 + 3 -5x = 1 + 3 Combine like terms: 1 + 3 = 4 -5x = 4 Divide each side by '-5'. x = -0.8 Simplifying x = -0.8
| (3x-5)=2.5x+3(x-6) | | 1-10/13 | | 2x/5=5x+2/6 | | 4g-5-3-4g= | | 5n+34=-21 | | 4u=5(u-1)-3 | | 5*6*7/8 | | (2x)/5=(5x+2)/6 | | 9/3*6*4/9 | | .5x^2+.5x-6=y | | y=10/9*5+10 | | 9/3(6*4/9) | | -10z-5=-20z+1.6 | | y=10/9*4+10 | | 5x+4(-3x-5)=-22-5x | | 5-2b=3b-7b+25 | | 11/19/8/19 | | 4(x+1)-2(3x+5)=-3x+1 | | 1-8/19 | | 54.3x=29 | | 5y-6+y=15+4y-5y | | 78+y=80 | | 80+83+71+61+95+y=80 | | (5w+24)+(2w+13)=155 | | 4=-3x-8 | | 3n=27-6(n-3) | | 2x^2+19x-4.9=0 | | 80+83+71+61+95+y=78 | | x^2+19x-4.9=0 | | 2/3*(x/b+1)=3/4(x/b-1) | | 2/3(6)-4/7=4 | | x/2(18+2x) |